Haka as a Representation of Cultural Philosophy through Rugby - Abdul Mahfudin Alim (Budapest International Research and Critics University, 2022)
Haka dance is a ritual of the indigenous Maori tribe of New Zealand. This dance is performed not only in the form of a dance alone but is also often referred to as a Maori ceremonial challenge that is carried out before war or to honor someone. The All Black Team is the name of the New Zealand National Rugby team. The New Zealand Rugby Team has long danced the Haka in front of its opponents before the match started. Haka dance makes the audience get carried away by the energy and charm of Haka when they see the All Black team competing. In Rugby Haka matches are played in groups and usually represent a display of pride, strength and unity of a Maori tribe. This Haka dance attraction is often awaited by Rugby fans every time New Zealand plays in a Rugby tournament event. When dancing the Haka they show their chivalry traditions with expressions that frighten their opponents with loud and passionate voices that can be heard by all the spectators in the stadium. The dance is performed by being led by one person who is in command with various movements such as sticking out the tongue, hitting the palms of the hands and feet or stomping the feet on the ground. Haka has earned a place of its own and become an attraction in the era of contemporary sport and professional Rugby. This is an interesting phenomenon to be discussed to see Haka's philosophy as a representation of the All Black team in Rugby matches through a literature review.